Directed-Mutagenesis and Deletion Generated through an Improved Overlapping-Extension PCR Based Procedure - Kanoksilapatham, Wirojne; González, Juan M.; Robb, Frank T. (Science, Engineering and Health Studies, 2013)
Generating either single or multiple point mutations and producing deletions and insertions into targetDNA sequences are critical and widely used experimental procedures in molecular biological studies. This articlepresents a modified mutagenesis protocol based on an overlapping-extension PCR amplification method. Theprocedure benefits from the design of mutagenic primers to generate overlapping megaprimers without the needfor intermediate purification to remove unused primers. Unused primers are diluted out during the successiveamplification-extension reactions. A key success to this modified method is the use of two flanking primers afterthe overlapping extension reaction. The use of Pfu DNA polymerase increases, compared with Taq DNApolymerase, amplification accuracy. The proposed procedure represents a simple and efficient method thatintroduces many types of mutations into specific target DNA fragments and creates either hybrid DNA fragmentsor internal nucleotide deletions.